Information Aggregation in Standing and Ad Hoc Committees - Ali, S. Nageeb; Goeree, Jacob K; Kartik, Navin; Palfrey, Thomas R (American Economic Review, 2008)
Information Aggregation in Standing and Ad Hoc Committees by S. Nageeb Ali, Jacob K. Goeree, Navin Kartik and Thomas R. Palfrey. Published in volume 98, issue 2, pages 181-86 of American Economic Review, May 2008